2020
DOI: 10.12688/f1000research.22306.1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and prevention behavior related to HIV/AIDS among students of a college in Lao-PDR: a cross-sectional study

Abstract: Background: Inadequate knowledge, negative attitudes towards people living with HIV/AIDS and risky practices are related to the spread of HIV infection. This study aimed to explore and test associations between knowledge, attitude and AIDS prevention behavior among students in Kham Mouane Technical-Vocation College, Lao People’s Democratic Republic. Methods: A cross-sectional, self-report questionnaire study was conducted in May 2018. Pearson's Chi-squared test and binary logistic regression was used to test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…As regards the demographic characteristics of participants in our study, there was a significantly larger number of female participants (67%), which was in accordance with the results of studies performed in Portugal (64%) and Laos (61.6%) ( 17 , 18 ). In our study, participants (medical students) were older (age of 21–30 years) (53.2 vs. 50.5%), which was the case with the medical students in China (the median age ranges from 23 to 29 years—(25 years) ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As regards the demographic characteristics of participants in our study, there was a significantly larger number of female participants (67%), which was in accordance with the results of studies performed in Portugal (64%) and Laos (61.6%) ( 17 , 18 ). In our study, participants (medical students) were older (age of 21–30 years) (53.2 vs. 50.5%), which was the case with the medical students in China (the median age ranges from 23 to 29 years—(25 years) ( 19 ).…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, plenty of information related to this particular topic is easily available via the Internet data services. This also happened to be the case with the students in Malaysia (77.3%) ( 15 ), and medical students in Laos as well (76.6%), who gained most of their knowledge on the Internet ( 18 ). The nonmedical students in our study acquired knowledge from daily newspapers (79.4%), which was also the case with the Turkish students, who acquired knowledge from newspapers, magazines, and books as well ( 16 ).…”
Section: Discussionmentioning
confidence: 82%
“…There were many negative stigma issues: more participants in this study believed that child who were HIV positive should not have entitled to an education. This results similar Wongkongdech, et al, [10] The participants' attitude about HIV/AIDS was very poor ; less than half participants in this study said that A child with AIDS is entitled to an education; which represent (20%) while (76%) said that A child with AIDS is not entitled to an education.. A total of 200 participant students in this study, only 10 % they think HIV patients can live with the community with normal life, whereas (88%) respondents indicated that they think HIV patients should be isolated from the community and this agree with [10] (3%) only were knew there are treatment sites to provide treatment for AIDS patients in Yemen; while (90%) were don't know about it.…”
Section: Impact Of Education On Knowledge and Attitudes Towards Hiv/aidssupporting
confidence: 90%
“…Globally, HIV is one of the main problems with regard to public health and, this infectious disease is the fourth cause of mortality in the world [4][5][6][7][8][9][10][11]; despite progress in diagnosis, treatment, and pre-vention, but HIV/AIDS is still a serious public health challenge [5], especially in the youth category.…”
Section: Introductionmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) organization states that the number of college students diagnosed with AIDS increases by 30 to 50% every year 25 . In Brazil, although there are no epidemiological data on the incidence of this condition in the university population, several studies show that these individuals are more susceptible to the disease due to risky behaviors and low knowledge of prevention measures such as condom use [26][27][28] .…”
Section: Discussionmentioning
confidence: 99%